Peran Media Sosial Sebagai Variabel Moderasi dalam Pengaruh Harga dan Kualitas Produk Terhadap Keputusan Pembelian Di Thrift Shop Kota Gorontalo - Amlaiya, Indriyani; Rahmisyari, Rahmisyari; Arifin, Arifin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study aims to analyze the effect of price and product quality on purchasing decisions with social media as a moderating variable on thrift shop consumers in Gorontalo City. The phenomenon of increasing consumer interest in used clothing products (thrift) encourages the need for a deeper understanding of the factors that influence purchasing decisions. This study uses a quantitative approach with a survey method and Partial Least Squares Structural Equation Modeling (PLS-SEM) analysis technique. The sample in this study were consumers from three thrift shops active on social media, namely Meltik Store, Mokoapa Store, and J&D Store. The results showed that price had a positive and significant effect on purchasing decisions, while product quality had a negative and insignificant effect. Social media was shown to significantly moderate the relationship between price and purchasing decisions, but did not strengthen the effect of product quality on purchasing decisions. These findings indicate that in the context of thrift shops, purchasing decisions are more influenced by price aspects and perceptions formed through social media than by the quality of the product itself. This emphasizes the importance of an effective digital marketing strategy in influencing consumer behavior, especially through interesting and relevant social media content.